6(2-b)=-60

Simple and best practice solution for 6(2-b)=-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2-b)=-60 equation:


b in (-oo:+oo)

6*(2-b) = -60 // + 60

6*(2-b)+60 = 0

6*(2-b)+60 = 0

72-6*b = 0

72-6*b = 0

72-6*b = 0 // - 72

-6*b = -72 // : -6

b = -72/(-6)

b = 12

b = 12

See similar equations:

| 7(3+6t)=105 | | 4(1n+8)=48 | | 3(-4n+10)=-78 | | 4(5+6b)=308 | | 2(-7x+10)=6 | | 3(2x+9)=87 | | 6(3-3x)=0 | | 7(3m+3)=0 | | 3(1b-5)=3 | | 4(1w+8)=64 | | 3(7n+5)=225 | | 6(2-d)=42 | | 4(6-4m)=8 | | 3(-2a-10)=-60 | | 4(10+7b)=-212 | | 7(1t+6)=14 | | 6(10+2x)=180 | | 2(1x+3)=8 | | 7(3-4x)-5(2x+8)=0 | | 4(6m+3)=-276 | | 6(4+7d)=192 | | 5(2a+8)=40 | | 3(-1a-1)=-33 | | 6(-7b-1)=288 | | 5(2x-3)-3(x-2)=0 | | 2(7k+2)=-52 | | 7(9+6a)=357 | | 6(-3x+2)=-78 | | 2(9+5w)=138 | | 2(2-5b)=104 | | 3(5b+1)=18 | | 6(-1m+5)=-36 |

Equations solver categories